A contextual framework for primary education: fostering information literacy in Pakistan. Issue 3 (1st April 2019) - Batool, Syeda Hina; Webber, Sheila
Abstract : Purpose: This study aims to contribute theoretically in the information literacy (IL) literature by presenting process-based framework at the primary education level. This study also investigated school children's information-related tasks, their favored information sources and IL skills. Design/methodology/approach: The study utilized qualitative research approach and multiple nested sequential case study design to explore the phenomenon. Findings: The majority of children from public, private trust and unregistered schools were unable to present, organize, use and understand main ideas of given information. However, the elite economic class school children had good IL skills with few exceptions. Based on research findings, a process-based IL framework has been proposed at the primary education level. Research limitations/implications: The present study proposed a process-based IL framework which has practical implications for parents, librarians, teachers and policymakers. Originality/value: The paper is based on doctoral research which is of significance to information professionals and educators.